Comparing Orientation Position in Close-Range Photogrammetry for the Documentation of Waruga Cultural Heritage as 3D Objects - Salaki, Deiby Tineke; Latumakulita, Luther Aleander; Sintaro, Sanriomi; Islam, Noorul (Jurnal Teknik Informatika (Jutif), 2025)
Waruga is a distinctive cultural artifact found exclusively in the Minahasa region. Despite its historical and cultural significance, efforts to preserve Waruga remain inadequate. Many structures have been left neglected, covered in fungi, or even damaged over time. Additionally, government-led relocation initiatives have contributed to the loss of their original form, further threatening this invaluable Minahasa cultural heritage. This study aims to examine the impact of photographic orientation in the creation of 3D models using close-range photogrammetry techniques. The resulting 3D models will be displayed on a digital platform to support the preservation and promotion of Minahasa culture. The photography process was divided into two categories: point-of-view shots and high-angle shots. Findings indicate that the optimal angle for point-of-view shots is 15 degrees downward, while for high-angle shots, it is 30 degrees downward. Furthermore, comparative analysis of Waruga structures with varying shapes demonstrates that portrait orientation yields 3D models that more accurately resemble the original objects compared to landscape orientation when using the same number of images. The study concludes that portrait orientation is the most effective approach for 3D reconstruction of Waruga, offering advantages such as faster processing times and reduced file sizes. In contrast, landscape orientation presents challenges, including difficulties in capturing intricate details, increased processing time, and larger file sizes. These findings provide valuable insights into optimizing digital preservation techniques for Waruga and other cultural heritage artifacts.